International migration: concepts, models and state policies - Cebrián, J.A. A.; Bodega, M. ªI.; López-Sala, A.M. M. (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The intensification of international migratory flows in recent years has provoked much thinking as to what might be an appropriate national migratory policy. Following this tendency, in this article we present several considerations relating to the ethical implications of migratory policies. Our point of departure for this discussion consists in the analysis of two concepts, which we believe differ in meaning. We refer to the terms solidarity and citizenship, whose function and meaning in «politically correct» discourse (undefined and undefinable) we study in this article. Following this we deal with the different models of the state in the Western world. In this way the understanding of the cultural and political factors of international migration which we analyse in the final section of the article is made easier.